SUCCESSFUL MANAGEMENT OF MACERATED FOETUS IN A JAFFARABADI BUFFALO- A CASE REPORT - PARMAR, K H; RAVAL, R J; VALA, K B; BORKHATRIYA, D N (The Indian Journal of Animal Reproduction, 2022)
SUCCESSFUL MANAGEMENT OF MACERATED FOETUS IN A JAFFARABADI BUFFALO- A CASE REPORT.